Experimental analysis of the efficiency of tungsten inert gas (TIG) machining for different materials - Ong, Wei Koon (School of Materials Engineering, University Malaysia Perlis, 2010)
This paper presents an experimental study of efficiency of Tungsten Inert Gas (TIG) with various parameters in different materials. The experiments will base on Design of Experiment with the Taguchi Method. Experiments are carried out by utilizing the combination of machining parameters based on L9 Taguchi orthogonal design with four parameters which is current, pressure, welding speed and arc distance. Each parameter will affect the surface roughness of materials. ANOVA analysis used to identify optimum parameters that produce the best Surface.